Effect of Atmospheric Corrosion Toward Corrosion under Insulation (CUI)- A Case Study - Letchumanan, Ruvanraj; Dr. Fazimah Binti Mat Noor (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Corrosion under insulation (CUI) can be classified as major problem. It is typically difficult to identify as it lies hidden under insulation material. Besides that, Corrosion under insulation (CUI) happened and observed between the metal surface and the insulation on that surface as a result of water penetration. One of the problems is the pH and temperature. Different temperature can lead to a different result of CUI. It is depending on the type of material that been used as the insulator for pipe. This investigation was conducted based on the previous research where all the results to gain corrosion rate based on ASTM G189-07 were analyzed. This study only focused on two environmental factors which were pH and surrounding temperature. The results were analysed and the relationship between temperature, pH to the corrosion rate was established based on the previous research. Besides that, Scanning Electron Microscope (SEM) and Energy Dispersive X-ray (EDX) and X-ray Diffraction (XRD) were used to investigate the corrosion properties. The Linear Polarisation Test and Mass Loss Test were used to calculate the corrosion rate. The corrosion rates calculated based on mass loss data were much higher than those obtained from polarisation resistance data. The highest corrosion rate was observed at pH 3 and the lowest corrosion rate was noticed at pH 11. So, it can be concluded that the higher the temperature the higher the corrosion rate, while for the pH, the higher the pH, the lower the corrosion rate.